Efek Antiinflamasi Jus Bawang Putih terhadap Kadar C-Reactive Protein (CRP) pada Tikus Jantan Galur Sprague Dawley yang Diinduksi Karagenan: Anti-inflammatory Effect Of Garlic Juice On C-Reactive Protein (CRP) Levels In Carrageenan-Induced Male Sprague Dawley Rats - Nazia Azzahra; Hotlina Nainggolan (Jurnal Farmasi dan Farmakoinformatika, 2026)
Garlic (Allium sativum L.) is known to contain bioactive compounds with pharmacological potential, including anti-inflammatory activity. Inflammation is characterized by an increase in the biomarker C-reactive protein (CRP), which is produced by the liver in response to inflammatory processes. This study aimed to evaluate the anti-inflammatory effect of garlic juice on CRP levels in male Sprague Dawley rats induced with carrageenan. An experimental design was applied using 24 male rats divided into six groups: normal control, negative control (Na-CMC 1%), positive control (diclofenac sodium 4.5 mg/kgBW), and treatment groups receiving garlic juice at doses of 300, 400, and 500 mg/kgBW. Inflammation was induced by 1% carrageenan injection, and CRP levels were measured using the CRP-latex method. The results showed that garlic juice significantly reduced CRP levels compared with the negative control (p<0.05). The 500 mg/kgBW dose produced the most optimal effect, approaching the efficacy of the positive control. Therefore, garlic juice has potential as a natural anti-inflammatory agent effective in reducing CRP levels.